Research and Practice on the Teaching of Fundamentals of Mechanical Design Course in the Context of Emerging Engineering Education - Liu, Yanwen; Liu, Jiyu; Yang, Chunmei; Qu, Wen; Wang, Lifu (Journal of Educational Research and Policies, 2026)
In the context of Emerging Engineering Education, the teaching reform of Fundamentals of Mechanical Design course aims to address the insufficient integration of theory and application, the cognitive disconnect between abstract concepts and concrete practice, and the lag between fixed instructional hours and dynamic learning status. Guided by a student-centered philosophy, the course has implemented innovative blended teaching practices: constructing a curriculum ideology and politics case library aligned with national strategies, provincial needs, and institutional contexts, to foster students’ sense of mission and responsibility toward building an engineering powerhouse; reconstructing the teaching content system by integrating research projects, competition entries, and disciplinary frontiers; developing an online resource ecosystem featuring micro-lectures, mechanical animations, exercise question bank, and knowledge graphs; and leveraging real-time data from the smart teaching platform like ChaoXing and FiF to establish a precision feedback mechanism for learning analytics. The practical results validate the positive impact of these measures and demonstrate the effectiveness of the reform path, providing a valuable reference for teaching reforms in higher education.